2004
DOI: 10.1002/ange.200300588
|View full text |Cite
|
Sign up to set email alerts
|

Offene Metallcarboxylat‐Architekturen

Abstract: Alumosilicate und Metallphosphate sind die wichtigsten Beispiele für anorganische Materialien mit offenen Gerüsten. In den letzten Jahren stieß zu dieser Gruppe die Familie der Metallcarboxylate, zu der nicht nur Mono‐ und Dicarboxylate von Übergangs‐, Seltenerd‐ und Hauptgruppenmetallen, sondern auch eine Vielzahl von Hybridstrukturen zählen. Einige Carboxylate weisen neuartige magnetische Eigenschaften und Adsorptionseigenschaften auf. Mithilfe von Dicarboxylaten und verwandten Verbindungen kann man effektiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
7

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(64 citation statements)
references
References 473 publications
(215 reference statements)
1
56
0
7
Order By: Relevance
“…Some subfields of inorganic molecular chemistry can come quite close to this state of the art in those cases in which a particular target configuration can be realized by specific reaction routes based on well-understood procedures, for example, employing electronic or steric effects and the use of reaction steps with high directionality such as salt eliminations. [15] Currently, the field of "coordination polymers" [16,17] (a term coined already in 1964 [18] ) is burgeoning worldwide [8,19,20] and boasts truly spectacular results [21,22] (e.g. Figure 1 in Ref.…”
Section: The Concept Of the Energy Landscape Of Chemical Systemsmentioning
confidence: 99%
“…Some subfields of inorganic molecular chemistry can come quite close to this state of the art in those cases in which a particular target configuration can be realized by specific reaction routes based on well-understood procedures, for example, employing electronic or steric effects and the use of reaction steps with high directionality such as salt eliminations. [15] Currently, the field of "coordination polymers" [16,17] (a term coined already in 1964 [18] ) is burgeoning worldwide [8,19,20] and boasts truly spectacular results [21,22] (e.g. Figure 1 in Ref.…”
Section: The Concept Of the Energy Landscape Of Chemical Systemsmentioning
confidence: 99%
“…Metal carboxylates are particularly interesting since they not only form open-framework structures, but also because the carboxylate group may act as a linker between inorganic moieties [1]. α, ω-Alkane-dicarboxylates, such as succinate [suc 2− , (C 4 H 4 O 4 ) 2− ], have conformational freedom, and they can give novel frameworks, with for instance bidentate and monodentate linking modes, cis-cis, trans-trans and cis-trans orientation etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the presence of infinite M-O-M connectivities in metal dicarboxylate structures enables the electronic and magnetic exchange in one, two 0932-0776 / 10 / 0600-0695 $ 06.00 c 2010 Verlag der Zeitschrift für Naturforschung, Tübingen · http://znaturforsch.com or three dimensions [1], but the M-O-C-O-M pathway also needs to be taken into account for weak coupling [16]. Furthermore, it has ben reported that magnetic exchange interactions through hydrogen bonds are also possible [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, they are used as antitumor drugs [1] and as building blocks for metal-organic framework materials, [2] and they are found in aerosol particles comprising photochemical smog.[3] Isolated dicarboxylate dianions are stable in the gas phase and serve as model systems for multiply charged anions. [4,5] The presence of two charge centers separated by a hydrophobic, aliphatic chain also makes them ideal for studying charge screening and solventmediated effects.…”
mentioning
confidence: 99%